2011
DOI: 10.1002/pola.24792
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and fluorescent properties of model compounds for conjugated polymer containing maleimide units at the main chain

Abstract: 2,3‐Diaryl substituted maleimides as model compounds of conjugated maleimide polymers [poly(RMI‐alt‐Ar) and poly(RMI‐co‐Ar)] were synthesized from 2,3‐dibromo‐N‐substituted maleimide (DBrRMI) [R= cyclohexyl (DBrCHMI) and n‐hexyl (DBrHMI)] and aryl boronic acid using palladium catalysts. To clarify structures of conjugated polymer containing maleimide units at the main chain, 13C NMR spectra of 2‐aryl or 2,3‐diaryl substituted maleimides were compared with those of N‐substituted maleimide polymers. Copolymers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…28 Previous reports have shown that incorporation of the maleimide group into extended p-systems gives a range of dyes with fluorescence quantum yields (F f ) of up to 100%, emission maxima ranging from 460-680 nm, and often large Stokes shifts (4100 nm). [31][32][33][34][35][36][37] There are also scattered reports of emissive maleimides with heteroatom substitutions, [38][39][40][41] although a thorough investigation has been lacking. Herein we detail the spectroscopic characterisation of monoaminomaleimides (MAMs), and aminobromomaleimides (ABMs) synthesised by an addition-elimination reaction with monobromomaleimide and 2,3-dibromomaleimide, 42 in analogy to DTMs (Scheme 1).…”
mentioning
confidence: 99%
“…28 Previous reports have shown that incorporation of the maleimide group into extended p-systems gives a range of dyes with fluorescence quantum yields (F f ) of up to 100%, emission maxima ranging from 460-680 nm, and often large Stokes shifts (4100 nm). [31][32][33][34][35][36][37] There are also scattered reports of emissive maleimides with heteroatom substitutions, [38][39][40][41] although a thorough investigation has been lacking. Herein we detail the spectroscopic characterisation of monoaminomaleimides (MAMs), and aminobromomaleimides (ABMs) synthesised by an addition-elimination reaction with monobromomaleimide and 2,3-dibromomaleimide, 42 in analogy to DTMs (Scheme 1).…”
mentioning
confidence: 99%
“…One‐pot transformation of 2,3‐dichloromaleic anhydride ( 2 ) into monosubstituted imide 3‐ p ‐toluidino‐2‐chloro‐ N ‐ p ‐tolylmaleimide ( 3 ) proceeded with two equivalents of p ‐toluidine in toluene under reflux for 24 h. Subsequently, Pd‐catalyzed Suzuki–Miyaura coupling reaction17 of 3 and phenylboronic acid at 90 °C for 5 h led to 4 after purification by silica‐gel chromatography and recrystallization from dichloromethane and methanol 18. Nucleophilic substitution of 3 with p ‐thiocresyl was performed in diethyl ether at 0 °C, and subsequent addition of triethylamine lead to a yellowish precipitate of 5 after stirring at room temperature for 16 h 19…”
Section: Resultsmentioning
confidence: 99%
“…One-pot transformation of 2,3-dichloromaleic anhydride( 2) into monosubstituted imide 3-p-toluidino-2-chloro-N-p-tolylmaleimide( 3)p roceededw ith two equivalents of p-toluidine in toluene under reflux for 24 h. Subsequently,P d-catalyzed Suzuki-Miyaura coupling reaction [17] of 3 and phenylboronic acid at 90 8Cfor 5hled to 4 after purificationbysilica-gelchromatography and recrystallization from dichloromethane and methanol. [18] Nucleophilics ubstitution of 3 with p-thiocresyl was performed in diethyle ther at 0 8C, and subsequenta ddi-tion of triethylamine lead to ay ellowish precipitate of 5 after stirring at room temperature for 16 h. [19] Compound 2 was converted to 2,3-dichlo-N-arylmaleimides 6a-6c with one equivalent of p-substituted aniline in toluene under reflux for4h. [20] The same synthetic procedure as that of 5 resulted in 7a-7c.I ti sn oteworthy that purification only required washing with methanol, except for 4.T he chemical structures of the newly synthesized compounds were confirmed by 1 Ha nd 13 CNMR spectroscopy and high-resolution mass spectrometry.…”
Section: Synthesis Of Maleimided Yesmentioning
confidence: 99%
“…Since its first utility in protein modification and bioconjugation as demonstrated by James R Baker and Stephen Caddick [1,2], a wide variety of thiolated molecules have been substituted onto DBM such as peptides [2][3][4], proteins [2,5,6] and polymers [7,8]. DBM's utility has been further expanded as a fluorescent tag; when small alkyl chains are substituted to the DBM molecule, the resulting conjugate exhibits bright fluorescence in a range of solvents [9,10]. DBM also features a unique ability to exchange with an excess of thiols.…”
mentioning
confidence: 99%